O02.2 Oropharyngeal and genital gonorrhoea among heterosexuals who report sexual contact with partners with gonorrhoea. (14th July 2019) - Chow, Eric; Chen, Marcus; Williamson, Deborah; Bradshaw, Catriona; Trumpour, Sabrina; Howden, Benjamin; Fairley, Christopher
Abstract : Background: Recent evidence has shown that the oropharynx may be the primary driver for gonorrhoea transmission among men who have sex with men, but there have been very limited studies on heterosexuals due to lack of routine screening of oropharyngeal gonorrhoea. The aim of this study was to examine oropharyngeal gonorrhoea positivity among heterosexuals reporting contact with sexual partners with gonorrhoea. Methods: At the Melbourne Sexual Health Centre, all heterosexual individuals reporting contact with sexual partners with gonorrhoea are tested for genital gonorrhoea. In May-2017, MSHC also included screening for oropharyngeal gonorrhoea in heterosexuals reporting sexual contact with partners with gonorrhoea. All contacts of gonorrhoea cases among heterosexuals between May-2017 and November-2018 were reviewed. Site-specific gonorrhoea positivity was also calculated. Results: 191 heterosexual contacts (102 males and 89 females) were reviewed. The median age was 28 [IQR=24–33] years. The gonorrhoea positivity in male was significantly higher at the oropharynx compared to urethra (17.6% [95% CI: 10.8–26.4%] versus 2.0% [0.2–6.9%]; p < 0.001); and higher at the oropharynx in female compared to cervicovaginal site (46.1% [35.4–57.0%] versus 36.0% [26.1–46.8%]; p =0.056). Of the 100 males who did not have genital gonorrhoea, 17 (17.0% [10.2–25.8%]) tested positive at the oropharynx. Of the 55 females who did not have genital gonorrhoea, 21 (23.6% [15.2–33.8%]) tested positive at the oropharynx. Infection at both the oropharynx and genital sites was not associated with sex worker status in females. Overall, 89.5% and 39.6% of gonorrhoea in males and females were detected only in the oropharynx, respectively. Conclusion: Multiple sites of gonococcal infection are more common in female contacts than in male contacts. Approximately 90% and 40% oropharyngeal infections would have been missed in males and females, respectively, by genital-only screening among heterosexuals reporting contact with sexual partners with gonorrhoea. Oropharyngeal gonorrhoea screening among heterosexual contacts of gonorrhoea is important to prevent ongoing transmission. Disclosure: No significant relationships.